Crosslinker effect on composite synthesis of alginate with activated carbon and nanocellulose as micronutrient slow-release fertilizer - Zainuddin Muchtar; Siti Rahmah; Moondra Zubir; Putri Faradilla; Rini Selly; Ahmad Shafwan Pulungan; Lisna Efiyanti; Riska Cahyati; Atikah Nur Syahirah (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Oil Palm Empty Fruit Bunches (OPEFB) solid waste has potential as a feedstock to be transformed into nanocellulose and activated carbon. In this study, we observed the effect of various compositions of activated carbon, alginate, and nanocellulose on the production of micronutrient slow-release fertilizer composites.